“Today I Die like Jesus Christ”: An Analysis of Ressentiment in Perceptions, Motivations and Justifications of Violent Extremist Manifestos - Capelos, Tereza (Terrorism and political violence, 2025)
Far-right extremists distribute digital manifestos alongside their violent attacks as a method of sensationalizing their acts, dispersing their ideology, and garnering followers. This study sheds light on the psychological characteristics of the perceptions, motivations, and justifications evident in their manifestos. We analyze their self-perceptions as martyrs, warriors, or saviors, their perceptions of world injustice, their motivations of grievance, humiliation, seeking revenge and defense and their justifications founded on absolutist thinking, moral disengagement and us vs. them divisions—mapping out how they deliver their message through the emotional mechanism of ressentiment. We show the complexity of the manifestos content, particularly in reference to the way extremists present themselves as martyrs, warriors, or saviors, the pervasive reference of grievances and frustrations, the shallow social bonds and outgroup dehumanization, their strong motivations to seek revenge and defend, and the morally disengaged justifications of their intentions and actions. This project addresses an important gap in extant literature and offers valuable insights to academics and practitioners on the discourses that promote mobilization and engagement with political violence.